2023
DOI: 10.3389/fneur.2023.1131085
|View full text |Cite
|
Sign up to set email alerts
|

Poor nutritional status is associated with incomplete functional recovery in elderly patients with mild traumatic brain injury

Abstract: BackgroundThe geriatric nutritional risk index (GNRI) is a simple index for evaluating the nutrition status of elderly patients. Many investigations have demonstrated that this index is associated with the prognosis of several diseases. This study aims to identify the relationship between the GNRI and recovery in elderly mild traumatic brain injury (mTBI) patients.MethodsA total of 228 mTBI patients older than 65 years were included in this study. mTBI was defined as an injury to the brain with a loss of consc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Similarly, Bao et al's study revealed that among elderly patients experiencing early neurological deterioration following acute ischemic stroke, 48.3% were at risk of malnutrition according to GNRI [26]. In another study, the GNRI assessment revealed a malnutrition risk of approximately 42.5% (97/228) among elderly patients with mild traumatic brain injury [27]. These results above suggest that brain injury in elderly patients is often accompanied by malnutrition.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Similarly, Bao et al's study revealed that among elderly patients experiencing early neurological deterioration following acute ischemic stroke, 48.3% were at risk of malnutrition according to GNRI [26]. In another study, the GNRI assessment revealed a malnutrition risk of approximately 42.5% (97/228) among elderly patients with mild traumatic brain injury [27]. These results above suggest that brain injury in elderly patients is often accompanied by malnutrition.…”
Section: Discussionmentioning
confidence: 78%
“…A positive correlation emerged between GNRI scores and GOS scores(P < 0.001), indicating a nutritional status may be signi cantly associated with recovery and long-term outcomes in brain abscess patients. Several studies also have demonstrated a correlation between elevated malnutrition risks and adverse clinical outcomes in geriatric patients [27,31]. It can be seen that in the process of diagnosis and treatment of geriatric diseases, the assessment of nutritional status cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Bao et al’s study revealed that among older patients experiencing early neurological deterioration following acute ischemic stroke, 48.3% were at risk of malnutrition according to GNRI ( 30 ). In another study, the GNRI assessment revealed a malnutrition risk of approximately 42.5% (97/228) among older patients with mild traumatic brain injury ( 31 ). These results above suggest that brain injury in older patients is often accompanied by malnutrition.…”
Section: Discussionmentioning
confidence: 96%
“…A positive correlation emerged between GNRI scores and GOS scores ( p < 0.001), indicating a nutritional status may be significantly associated with recovery and long-term outcomes in brain abscess patients. Several studies also have demonstrated a correlation between elevated malnutrition risks and adverse clinical outcomes in geriatric patients ( 31 , 35 ). It can be seen that in the process of diagnosis and treatment of geriatric diseases, the assessment of nutritional status cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%